Cyanine Nanocages Activated by Near-Infrared Light for the Targeted Treatment of Traumatic Brain Injury - Black, Caroline E.; Zhou, Eugene; DeAngelo, Caitlin M.; Asante, Isaac; Louie, Stan G.; Petasis, Nicos A.; Humayun, Mark S. (Frontiers in Chemistry, 2020)
Traumatic brain injury (TBI) is a common and prevalent condition that affects large numbers of people across a range of ages. Individuals engaging in physical activities and victims of accidents are at a higher risk for TBI. There is a lack of available treatment specifically for TBI. Given the difficulty to determine its precise location in the brain, TBI remains difficult to fully diagnose or treat. Herein, we disclose a novel strategy for directing therapeutic agents to TBI sites, without the need to determine the precise location of the TBI activity in the brain. This novel approach is based on the use of a cyanine dye nanocage carrying Gabapentin, a known TBI therapeutic agent. Upon exposure of the cyanine nanocage to near-infrared light, the local release of Gabapentin is triggered, selectively at the TBI-affected site.